PENYUSUNAN DAN PENDAMPINGAN PENERAPAN STANDARD OPERATING PROCEDURE (SOP) PENGOLAHAN TANAH SAYUR ORGANIK PADA CV. REJA MAYUR - Rahayu, Niken Calista; Yuliati, Nuriah (Jurnal Pengabdian Agro and Marine Industry, 2023)
CV. Reja Mayur in his cultivation process already has a standard or Standard Operating Procedure (SOP), but the Standard Operating Procedure (SOP) has not been documented in writing. This results in workers often making mistakes, especially in the land preparation stage. Where these errors will result in agricultural production results that are not optimal. The purpose of this community service activity is to produce a written document explaining the Standard Operating Procedure (SOP) for processing organic vegetable soil at CV. Reja Mayur. This service is carried out by interviews and observations at the business location. The results of this service are Standard Operating Procedure (SOP) documents for land management and providing assistance in the application of Standard Operating Procedures (SOP) which are expected to make worker performance more consistent and minimize errors so that agricultural production results can be maximized.